THE RELATIONSHIP BETWEEN THE OCCUPATIONAL FACTORS AND HEARING IMPAIRMENT IN PT. BINDER INDONESIA WORKERS: OCCUPATIONAL FACTORS AND HEARING IMPAIRMENT - Muzakir, Haris; Lorenzo, Khaerunisa Putri (STIKes Mandala Waluya Kendari, 2025)
Background: Industrial noise exposure is a significant occupational hazard, with prolonged exposure leading to irreversible noise-induced hearing loss (NIHL). This study examines the relationship between occupational factors (noise exposure, work tenure, hearing protective device usage, and worker age) and hearing impairment among production workers at PT Binder Indonesia, a manufacturing company with high-intensity noise levels (90–100 dBA). Methods: A cross-sectional analytic study was conducted with 176 male workers aged 20–65 years, exposed to ≥85 dBA noise for ≥5 years. Data were collected through noise level measurements (Sound Level Meter), hearing tests (Rinne, Weber, Schwabach), and questionnaires. Statistical analysis included chi-square tests and prevalence ratios (PR) with 95% confidence intervals (CI) using SPSS. Results: Hearing impairment was prevalent in 60.2% of workers. Significant relationships were found between work tenure >5 years (PR=1.640; 95% CI: 1.174–2.291; *p*=0.001) and age ≥40 years (PR=0.725; 95% CI: 0.576–0.913; *p*=0.014). Noise exposure (>85 dB) and hearing protective device usage showed no significant relationship (*p*>0.05). Conclusion: Long work tenure increases NIHL risk, while older age may have a protective effect, possibly due to adaptive measures. Despite high noise exposure, consistent use of protective devices did not significantly reduce impairment, suggesting the need for improved compliance and workplace interventions.